THE INDEPENDENCE BETWEEN IMPLICIT LEARNING AND GENERAL INTELLIGENCE IN CHILDREN OF SCHOOL AGE. - López-Ramón, María Fernanda; Introzzi, Isabel; Richard´s, Maria Marta (Anales de Psicología / Annals of Psychology, 2009)
The existing research about Reber's hypothesis of the inde-pendence between Implicit Learning (IL) and Intelligence in children populations, are scarce and confusing. We proposed to analyze the rela-tionship between IL, and General Intelligence in children from 7 to 11 years and to document empirical evidence in this one group of age using tests specifically created to evaluate a sample of children of school age. We studied 50 children of the city of Mar del Plata, Argentina. We tested infants in IL, Explicit Learning (EL) and General Intelligence. The ob-tained correlations, allowed us to add empirical evidence to Reber's hy-pothesis of the independence between IL and IQ. The implications of the results will be discussed in relation to the measurement of the Intelligence during the infancy and in relation to the compensating role of Implicit Learning in cases of explicit learning deficit.